PENGARUH RASIO ARUS KAS TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR KELOMPOK BASIC INDUSTRY AND CHEMICALS - Soesetio, Yuli; Anam, M. Khoirul (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2011)
This research purpose are to know the influence of cash flow ratio to stock return every windows periods. Cash flow ratio that used are OCFR,TDR, and CFROA that get from comparing between operational cash flow with current liabilities, total liabilities and total assets on 2008 th-2009 th. Stock return that used are stock return before, on, after, and around annual reports publication that devided become 16 window periods that are five days before publication, on publication, five days after publication, and five days around publication.Sample of this research are 22 of Basic Industry and Chemicals Manufacturing Companies financial statements on 2008th-2009th with purposive sampling tech. The data analyze that use is multiple linear regression. The results of this research are OCFR influence to stock return at the first day around publication, TDR influence to stock return on publication, CFROA influence to stock return at fifth day, fourth day, third day before publication and third day, fourth day and fifth day around publication. The cash flow ratio influence to stock return simultaneous at fourth day before publication with adjusted R square 14,4%, on publication (t0) with adjusted R square 20,9%, the first day after publication with adjusted R square 21,1% and around publication (first day with adjusted R square 23,3% and fourth day with adjusted R square 10,5%)Â